Enhancement of P2X3 Receptor-Mediated Currents by Lysophosphatidic Acid in Rat Primary Sensory Neurons - Qiao, Wen-Long; Li, Qing; Hao, Jia-Wei; Wei, Shuang; Li, Xue-Mei; Liu, Ting-Ting; Qiu, Chun-Yu; Hu, Wang-Ping (Frontiers in Pharmacology, 2022)
Lysophosphatidic acid (LPA), a lipid metabolite, plays a role in both neuropathic and inflammatory pain through LPA1 receptors. P2X3 receptor has also been shown to participate in these pathological processes. However, it is still unclear whether there is a link between LPA signaling and P2X3 receptors in pain. Herein, we show that a functional interaction between them in rat dorsal root ganglia (DRG) neurons. Pretreatment of LPA concentration-dependently enhanced α,β-methylene-ATP (α,β-meATP)-induced inward currents mediated by P2X3 receptors. LPA significantly increased the maximal current response of α,β-meATP, showing an upward shift of the concentration-response curve for α,β-meATP. The LPA enhancement was independent on the clamping-voltage. Enhancement of P2X3 receptor-mediated currents by LPA was prevented by the LPA1 receptor antagonist Ki16198, but not by the LPA2 receptor antagonist H2L5185303. The LPA-induced potentiation was also attenuated by intracellular dialysis of either G-protein inhibitor or protein kinase C (PKC) inhibitor, but not by Rho inhibitor. Moreover, LPA significantly changed the membrane potential depolarization and action potential burst induced by α,β-meATP in DRG neurons. Finally, LPA exacerbated α,β-meATP- induced nociceptive behaviors in rats. These results suggested that LPA potentiated the functional activity of P2X3 receptors in rat primary sensory neurons through activation of the LPA1 receptor and its downstream PKC rather than Rho signaling pathway, indicating a novel peripheral mechanism underlying the sensitization of pain.